Peranan Pendidikan Karakter dalam Membangun Sikap Tolerensi dan Kesadaran Sosial Siswa Sekolah Dasar Terhadap Teman Sebaya - Salgia Fitri; Sartono Sartono (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to determine how character education plays a role in fostering tolerance and social awareness in elementary school students, especially in their relationships with peers. The study was conducted using a qualitative approach through interviews and observations of teachers and students at SD IT Permata Kita. The results of data collection indicate that character education has a significant influence on changes in students' attitudes.